Dimensi Finansial Dalam Keberlanjutan Program Sanitasi Terintegrasi : Studi pada SPALDS Komunal dan SPALDS Individual Di Kota Tanjungpinang The Financial Dimension in the Sustainability of Integrated Sanitation Programs; A Study of Communal and Individua - yayuk yuliati; Tengku Said Raza'i; Dewi Haryanti; Agung Dhamar Syakti; Febrianti Lestari Lestari; Arief Pratomo Pratomo (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
Sustainability of an integrated sanitation program does not rely simply on infrastructure and social acceptance but also on the system’s ability to ensure operational financing and long-term operation and maintenance. The current study aims to analyze the financial aspect as the sustainability tipping point of an integrated sanitation program in Tanjungpinang City, focusing on communal and individual SPALD-S. A mixed-methods approach was applied through a sequential explanatory design, integrating a quantitative framework based on FIETS (financial, institutional, environmental, technical, social) and a qualitative analysis utilizing the CIPP evaluation model. The results indicated that the financial aspect exhibited the lowest performance among the dimensions. The communal SPALD-S system scored 27.5, and the individual SPALD-S scored 32.0; both fall within the unsustainable category. This variance in score did not alter the overall sustainability status. The qualitative analysis revealed that the financial dimension’s weakness was caused by the absence of an institutionalized operational financing mechanism, project-based funds dependency, and a lack of alignment with local budget planning. The study concluded that the financial dimension is the main bottleneck to sustainability. A shift in perspective from physical construction to strengthening a context-appropriate system of long-term financing is crucial.